Drug-Related Problems among Hospitalized Surgical Elderly Patients in China. (15th February 2021) - Meng, Long; Qu, Can; Qin, Xia; Huang, Huali; Hu, Yongsheng; Qiu, Feng; Sun, Shusen
Abstract : There is a lack of data on drug-related problems (DRPs) among elderly patients from surgical departments. The current study is aimed at identifying and categorizing types of DRPs and assessing the severities of the DRPs. Medication orders for hospitalized patients aged ≥65 years from six surgery departments were reviewed to determine DRPs over 6 months in a tertiary teaching hospital of Chongqing, China. DRPs were classified based on the Pharmaceutical Care Network Europe classification V8.02. The severity ratings of the DRPs were assessed using the National Coordinating Council for Medication Error Reporting and Prevention classification. A total of 53, 231 medication orders from 1, 707 elderly patients were reviewed, and 1, 061 DRPs were identified. Treatment safety (44.9%) was the most common DRP type. Drug selection (43.1%) and dose selection (43.1%) were the major causes of DRPs. A total of 75.1% of the DRPs were classified into severity categories B to D (causing no or potential harm), and 24.9% were classified as categories E to H (causing actual harm). DRPs are common in hospitalized elderly surgical patients. Pharmacists should provide medication order reviews in this vulnerable patient population.